THE ISSUE OF WORLD RECESSION POST PANDEMIC ON COMPANY STOCK RETURN INDEX LQ-45 2021-2022 - Kiki Widya Kirana; Wuryaningsih Dwi Lestari (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2023)
This research aimed to analyze the effect of the post-pandemic world recession issues in the form of Inflation, Exchange Rate, and Gross Domestic Product (GDP) on company stock registered on the Indonesia Stock Exchange (IDX). The analysis method used is multiple regression analysis. The population of this study is all corporate sectors listed consistently in the LQ-45 Index on the Indonesia Stock Exchange (IDX). The sample obtained as many as 41 samples selected using the purposive sampling method. The research result shows that partial Inflation has a positive and significant effect on company stock returns LQ-45 Index, The Exchange Rate has a negative and significant effect on stock returns for LQ-45 Index companies, and Gross Domestic Product (GDP) has no significant effect on stock-returns LQ-45 Index companies. Simultaneously, Inflation, Exchange Rates, and Gross Domestic Product (GDP) together have a significant effect on the Stock Return of LQ-45 Index companies.